Interview: artificial intelligence, Big Tech, and Regulation: between innovation and governmental control - Picker, Randal C. (2025)
This article explores the tensions between innovation and democratic control in the regulation of artificial intelligence and Big Tech. While Europe adopts proactive regulatory frameworks like the Digital Markets Act, leveraging its tradition of legal sophistication, the United States maintains a reactive stance, relying on general principles and antitrust litigation. China, in turn, represents a distinct model of centralized governance. The discussion analyzes the limits of current legal tools –such as copyright, antitrust, and agency authority– while questioning whether traditional regulatory justifications remain valid in the digital era. The text also reflects on the ideological and political drivers behind current regulatory trends and raises the challenge of measuring Big Tech power beyond market metrics.